THE AUTHORITY OF THE SUPREME COURT REGARDING THE MATERIAL EXAMINATION OF THE ACEH QANUN - Fauzi Iswahyudi (NOMOI Law Review, 2023)
Problems position qanun aceh is equated with nomenclature ' Regional Regulation ' in Article 7 paragraph (1) of the Law Number 12 of 2011 concerning Formation Regulation Legislation , besides That need studied is qanun can tested in Court great . Method research used _ that is juridical normative . Results study show that Article 235 paragraph (2) of Law Number 11 of 2006 concerning the Government of AcehÂ arrange that Government can cancel conflicting qanuns _ with : a. interest general ; b. interqanun ; and c. regulation more legislation _ high , except another set in Constitution this . More carry on Chapter Article 235 paragraph (3) regulates that qanun can tested by Court great in accordance with regulation legislation . (4) Qanuns as meant on paragraph (3) which regulates about implementation Islamic Shari'at only can canceled through test material by Court great .